The shared burden of domestic violence: a qualitative study with informal supporters of survivors. (November 2016) - Gregory, Alison; Feder, Gene; Williamson, Emma
Abstract: Background: Domestic violence and abuse is experienced by 25% of women and has far-reaching health consequences for survivors. Most survivors access support from people around them, which has the potential to buffer against effects on physical and mental health of survivors, and to protect against future abuse. However, little research has directly assessed how impacts of domestic violence and abuse might diffuse to affect these informal supporters. The aim of this research was exploratory, investigating the effects on health and wellbeing in people who provide informal support to survivors of domestic violence and abuse. Methods: Qualitative interviews were conducted in the UK, between 2012 and 2013, with people who had, at any point during adulthood, supported a friend, relative, or colleague who was in an abusive relationship. Recruitment was via social media, radio, and flyers in community settings. Themes from a systematic review formed the basis of the topic guide, and participants gave written informed consent. Interviews were conducted face to face, by telephone, and with Skype. Transcripts were coded in NVivo (version 10), and a thematic analysis of narratives carried out: data were coded, arranged into themes by the first author, and refined in collaboration with coauthors, by the constant comparison method. The Research Ethics Committee in the School for Policy Studies at the University of Bristol approved the study. Findings: 23 participants were recruited and interviewed. Five major themes emerged from the analysis: psychological impacts (including anxiety, low mood, confusion, and anger), physical health impacts, relationship impacts, practical impacts, and being at direct risk of harm from the perpetrator. Factors that mediated the impacts experienced included the supporter's sex, the closeness of the relationship between supporter and survivor, the severity of abuse experienced by the survivor, and whether the survivor had children. Interpretation: The toll on informal supporters of survivors of domestic violence and abuse was multifaceted, often onerous, and frequently persistent. Scarce support is available for friends, relatives, and colleagues of survivors. These findings have practical and policy implications to recognise and meet the needs of these important informal supporters, and have informed a public health campaign across Bristol. Funding: This research was conducted as part of PhD study funded by the National Institute for Health Research School for Primary Care Research, and was hosted by the University of Bristol.